2011
DOI: 10.1128/jvi.05032-11
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Blood-Brain Barrier during Venezuelan Equine Encephalitis Virus Infection

Abstract: Venezuelan equine encephalitis (VEE) virus is a mosquito-borne alphavirus associated with sporadic outbreaks in human and equid populations in the Western Hemisphere. After the bite of an infected mosquito, the virus initiates a biphasic disease: a peripheral phase with viral replication in lymphoid and myeloid tissues, followed by a neurotropic phase with infection of central nervous system (CNS) neurons, causing neuropathology and in some cases fatal encephalitis. The mechanisms allowing VEE virus to enter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 31 publications
9
68
0
Order By: Relevance
“…Paracellular entry under these conditions may contribute to a second phase of CNS infection. Indeed, initial infection of CNS by VEEV via the olfactory route impairs the BBB leading to a CNS infection through hematogenous spread [161]. This observation was further supported by other studies where intracranial inoculation of mice with VEEV replicon particles resulted in increased expression of intercellular adhesion molecule 1 (ICAM-1) on BMECs, followed by BBB disruption [162].…”
Section: Entry Of Arboviruses Into the Cnssupporting
confidence: 73%
“…Paracellular entry under these conditions may contribute to a second phase of CNS infection. Indeed, initial infection of CNS by VEEV via the olfactory route impairs the BBB leading to a CNS infection through hematogenous spread [161]. This observation was further supported by other studies where intracranial inoculation of mice with VEEV replicon particles resulted in increased expression of intercellular adhesion molecule 1 (ICAM-1) on BMECs, followed by BBB disruption [162].…”
Section: Entry Of Arboviruses Into the Cnssupporting
confidence: 73%
“…2C), and the production of infectious virus particles (Fig. 2D) were not as elevated as those in BHK21 cells (MOI,5). As a quantitative measurement of the impact of pericytes on the endothelial barrier integrity during the course of JEV infection, we monitored the TEER (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neurotropic virus-associated neuropathy is characterized by the presence of infectious virus particles, immune cells, inflammatory mediators, and eventual neuronal dysfunction or destruction in the parenchymal tissues of the CNS. Generally, BBB integrity is compromised during infection, and this BBB disruption dictates the aforementioned alterations and brain injury in several neurotropic viruses (3)(4)(5)(6). Though most studies demonstrated the detrimental consequences of BBB breakdown during neurotropic virus infection, the opening of the BBB also prevents certain lethal viral CNS infections (7).…”
mentioning
confidence: 99%
“…RNA samples were then treated with DNase using the Turbo DNA-free kit (Ambion), following the manufacturer's protocol. Quantification of influenza virus strain PR8 hemagglutinin (HA) negative-strand RNA levels in the nasal tissues was performed by reverse transcription-PCR (RT-PCR) as has been described previously (47). Briefly, cDNAs were prepared using reverse transcription with oligo(dT).…”
Section: Methodsmentioning
confidence: 99%